1999
DOI: 10.1021/jm9806289
|View full text |Cite
|
Sign up to set email alerts
|

Highly Potent Cyclic Disulfide Antagonists of Somatostatin

Abstract: The search for synthetic analogues of somatostatin (SRIF) which exhibit selective affinities for the five known receptor subtypes (sst1-5) has generated a large number of potent agonist analogues. Many of these agonists display good subtype selectivities and affinities for the subtypes 2, 3, and 5, with very few selective for sst1 or sst4. Until the recent report by Bass and co-workers (Mol. Pharmacol. 1996, 50, 709-715; erratum Mol. Pharmacol. 1997, 51, 170), no true antagonists of somatostatin had been disco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
55
1
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 33 publications
2
55
1
1
Order By: Relevance
“…However, in perfused pancreata at 5.5 mmol/l glucose, DC-41-33 increased the second phase of insulin release by 34.6% (P ϭ 0.4). Although this compound shows 20-fold higher affinity to SSTR2 (A-cells) than SSTR5 (B-cells) (25), it is possible that the antagonist enhanced glucagon as well as insulin release in experiments with higher basal glucose in the perfusate that facilitates SST release. Significant enhancements of insulin secretion occurred in most but not all of our batch incubations of isolated islets at 2 mol/l DC-41-33.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…However, in perfused pancreata at 5.5 mmol/l glucose, DC-41-33 increased the second phase of insulin release by 34.6% (P ϭ 0.4). Although this compound shows 20-fold higher affinity to SSTR2 (A-cells) than SSTR5 (B-cells) (25), it is possible that the antagonist enhanced glucagon as well as insulin release in experiments with higher basal glucose in the perfusate that facilitates SST release. Significant enhancements of insulin secretion occurred in most but not all of our batch incubations of isolated islets at 2 mol/l DC-41-33.…”
Section: Discussionmentioning
confidence: 97%
“…DC-41-33 is a highly specific SSTR2 antagonist (25). In CHO cells transfected with human SSTRs, this compound binds competitively to SSTR2 with a binding affinity (K i ) of 26 Ϯ 3.1 nmol/l and displays selectivity for human SSTR2 over SSTR5 by factor 20 (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A potent and highly specific SSTR2 antagonist, DC-41-33, has been synthesized (8). Recently we used this antagonist to investigate whether paracrine interactions operate in pancreatic islets, and demonstrated that the arginine effect on glucagon release was markedly enhanced by DC-41-33 (K.C., D.H.C., S.E., submitted manuscript).…”
Section: Discussionmentioning
confidence: 99%
“…In rodents, somatostatin inhibits glucagon and insulin release via SSTR2 and SSTR5, respectively (6,7). A novel highly specific SSTR2 antagonist, DC-41-33, has recently been synthesized (8). When applied in both perifused isolated rat islets and isolated perfused rat pancreas, this compound enhances arginine-stimulated glucagon release nearly threefold, which implies that islet somatostatin exerts a pronounced paracrine effect on A cell secretion (K.C., D.H.C., S.E., submitted manuscript).…”
mentioning
confidence: 99%